INTERPERSONAL COMMUNICATION IN LEARNING PERSPECTIVE OF KORAN (The Study of Interpretation In QS: As Saffat 102-111) - Iis Sholihat Damanik, Achyar Zein, Ardiansyah (Pascasarjana UIN Sumatera Utara, 2019)
Abstract: This research aimed to describe about interpersonal communication in learning perspective of Koran (the study of interpretation in Q.S.: As saffat (102-111). The type of this research is library research with a qualitative approach. The research method used is the method of interpretation that is tahlily method. More over, the source of this research is Koran, Tafsir, and literature relating to the interpersonal communication in learning, while the technique of collecting the data was by collecting Mu’jam al-Mufahras lil Alfazil Alquran Karim, which was composed by Muhammad Fuad. Technique of analyzing the data was performed by using content analysis. The results of this research were interpersonal communication used by Prophet Ibrahim and Prophet Ismail to be dialogical, open, and empathy. Prophet Ibrahim as an educator, provides the best education for his children or learners with full loyalty. Thus, producing obedient children, obedient and patient when facing problems as well as words that are well organized and polite. Besides, the interpersonal methods of learning in Q.S. As-Shaffat 102-111 which is dialogue method, discussion, informative telecommunication, persuasive, and instructional method, used to dear call method, reward method, and exemplary method. Keywords: Interpersonal communication, Learning, Koran.